Inflammation and Fatty Degeneration in New Bone Formation in Patients with AS Treated with Anti-TNF Agents - Rizzo, Toni (MD Conference Express, 2012)
When the inflammation of ankylosing spondylitis (AS) subsides, it may be replaced by repair tissue and fatty lesions, a process that leads to osteoproliferation and development of syndesmophytes. This article presents results from the European Ankylosing Spondylitis Infliximab Cohort [EASIC] study, an open-label extension of the Ankylosing Spondylitis Study for the Evaluation of Recombinant Infliximab Therapy [ASSERT]. The objective of the EASIC study was to directly compare the effect of inflammation and fatty degeneration on the development of syndesmophytes in patients with AS after 5 years of anti-TNF therapy.